Analisis Nilai Tambah Kelapa Sawit Menjadi Crude Palm Oil (CPO) di PT. Surya Raya Lestari 1 Desa Bulu Mario, Kecamatan Sarudu, Kabupaten Pasangkayu Sulawesi Barat - Rudianto, Yenni; Rengkung, Leonardus Ricky; Maweikere, Audrey Julia Maria (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This study aims to: (1) describe the process of processing oil palm into Crude Palm Oil (CPO), and (2) calculate the added value of processing oil palm into Crude Palm Oil (CPO) at the palm oil mill of PT. Surya Raya Lestari 1. This research was conducted for 4 months starting from the preparation stage to the preparation of the report starting from February 2023 to June 2023, Primary data is data taken through direct observation and interviews with the head of the price section and the head of the factory of PT. Surya Raya Lestari 1. This research uses descriptive analysis of the Hayami model. Based on the results of the study, the added value generated from processing Palm Oil into CPO at PT Surya Raya Lestari 1 is Rp.158.71 / kg of raw material with a value-added ratio of 8.156 percent. The profit obtained from processing Palm Oil into CPO at PT Surya Raya Lestari 1 is Rp.133.161 / kg with a profit rate of 83.902 percent.